The Top Management's Role In Staff Motivation: Examining the Relationship between Identity Styles and Psychological Well-Being in Hellene University Students (Journal of Advances and Scholarly Researches in Allied Education, 2012)
A successful identity formation is related tobeing psychologically well (Erikson,1963).This link seems to be lost in theidentity style literature that focuses either on the maturity of the identitystyles, or on adaptive and maladaptive behaviour correlates of identity styles.In this study, we address this lost link. We administered the Identity Style Inventory(Berzonsky, 1992a) and the scales of Psychological Well-Being (Ryff,1989) to 230 Hellene University students. The Hellenic translations of the scales functioned appropriately. The findings suggest that, first, avoiding facing identity issues is negatively related to psychological well-being, and, second,when such issues are faced, the way of facing the Minot important.